[tex]f(x) = x^{2} + 5[/tex] [tex]g(x) = \frac{x + 5}{5} [/tex]
First find gf(x) by substituting the expression for f(x) wherever there is an x in the g(x) function
[tex]gf(x) = \frac{( x^{2} + 5 ) + 5}{5} [/tex]
Simplify the equation and then substitute -3 where the x's are in gf(x)
gf(x) = [tex] \frac{ x^{2} + 10}{5} [/tex]
gf(-3) = [tex] \frac{(-3)^{2} + 10 }{5} [/tex]
= [tex] \frac{9 + 10}{5} [/tex]
= [tex] \frac{19}{5} [/tex]
Keen to note that if you worked f(-3) first and then substituted that into g(x) then you would get the same answer.